RECONSTRUCTION OF POLITICAL LAW ENFORCEMENT OF MONEY IN ELECTION CHALLENGES BASED ON PROGRESSIVE LAW CASE STUDY IN TEGAL CITY, SEMARANG AND DISTRICT OF PEMALANG - imawan imawan (Jurnal Pembaharuan Hukum, 2017)
Abstrac tElections, both presidential / vice-presidential elections, legislative bodies both at the center and in the regions until the regional head is colored by money politics, as a way of winning a presidential, legislative body or regional head candidate. A democracy that should be able to choose qualified candidates for leaders, in the presence of dirty practices such as money politics, produces only a leader who is indifferent to the people and corrupt. Law enforcement of money politics continues to be pursued, both in terms of legal substance, legal structure, and legal culture. Progressive law is an alternative politics problem, with the courage of law enforcers in the police, prosecutors, judges and other related institutions to the imposition of criminal and administrative sanctions.